AMADU BANSANG JOBARTEH; MASTER OF THE KORA, Eavadisc EDM 101, Cambridge Audio-Visual Ethnomusicological Archive, 1978. - Blench, Roger (International Library of African Music, 1983)
pages: 127
Keywords: African Music